Frequency of Depression and Anxiety among Patients with Psychogenic Non-Epileptic Seizures: - Ashjazadeh, Nahid; Kashani, Kaveh; Sahraian, Ali; Asadi-Pooya, Ali Akbar (Galen Medical Journal, 2014)
Background: Diagnosis of psychogenic non-epileptic seizures (PNES) particularly in patients with epilepsy poses a challenge to physicians to care. This study is aimed at determining the frequency of depression and anxiety among Iranian patients with PNES. Materials and Methods: Sixty patients with PNES and one hundred age-and-sex matching healthy controls were enrolled in this study from January 2010 to January 2011. Patients had at least one psychogenic non-epileptic seizure recorded during video-EEG monitoring in an epilepsy care unit of Namazi Hospital, Shiraz, Iran. Demographic data were collected and Iranian validated versions of Beck Depression and Anxiety Inventory-2 questionnaires were used. Statistical analysis was conducted using Mann-Whitney U-test, Pearson’s chi-square test and independent T test. P < 0.05 was considered statistically significant. Results: Of 60 PNES patients, 37 (61.7%) were female and 23 (38.3%) were male (P=0.767) and mean of the patients’ age was 24.9 ± 6.6 years (P=0.674). Among controls, 64 (64%) persons were female and 36 (36%) were male; mean age was 24.4 ± 2.1 years. Forty two patients (70%) and 36 controls (36%) had moderate to severe depression (P=0.001). Thirty eight patients (63.4%) and 10 controls (10%) had medium to high levels of anxiety (P=0.001). Conclusion: Frequency of depression and anxiety among patients with PNES is much higher than general population. Prompt diagnosis of these two common coexisting psychiatric disorders may help physicians for better evaluation and appropriate management of PNES patients. [GMJ. 2014;3(4):202-6]